A Full-Stack Gym Management System for Fitness Centers Using MERN Architecture - Ali Hasan; Nihal Patel; Mohsin Hasan (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The health and fitness industry is undergoing rapid digital transformation, with a growing demand for efficient tools to manage memberships, workout planning, and progress tracking. Traditional paper-based or spreadsheet-driven gym management methods often result in inefficiencies, human error, and limited engagement between trainers and members. This paper presents the design and implementation of a full-stack Gym Management System (GMS) developed using the MERN stack (MongoDB, Express.js, React.js, Node.js). The system integrates modules for user registration, membership renewal, fitness testing, workout planning, and historical progress tracking. Experimental evaluation demonstrates that the system enhances administrative efficiency, reduces membership churn through automated alerts, and provides transparent data access for both trainers and members. Results confirm the effectiveness of the proposed solution, and future enhancements such as mobile support, integration with wearable devices, and payment gateways are discussed.
Keywords: Gym Management System; MERN Stack; Fitness Tracking; Membership Automation; Full-Stack Development